2022
DOI: 10.1186/s43058-022-00370-7
|View full text |Cite
|
Sign up to set email alerts
|

Group Care in the first 1000 days: implementation and process evaluation of contextually adapted antenatal and postnatal group care targeting diverse vulnerable populations in high-, middle- and low-resource settings

Abstract: Background Group care (GC) improves the quality of maternity care, stimulates women’s participation in their own care and facilitates growth of women’s social support networks. There is an urgent need to identify and disseminate the best mechanisms for implementing GC in ways that are feasible, context appropriate and sustainable. This protocol presents the aims and methods of an innovative implementation research project entitled Group Care in the first 1000 days (GC_1000), which addresses thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A more child-friendly approach is recommended for general dentists. The Group Care (GC) model offered by child health clinics) model is a promising approach that fits parents’ wish for more help in parenting and managing their hectic family life [ 55 ]. Such a GC model helps strengthen families in parenting through conversations with peers from their social surroundings while backed by a professional leading the group [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more child-friendly approach is recommended for general dentists. The Group Care (GC) model offered by child health clinics) model is a promising approach that fits parents’ wish for more help in parenting and managing their hectic family life [ 55 ]. Such a GC model helps strengthen families in parenting through conversations with peers from their social surroundings while backed by a professional leading the group [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility criteria for papers to be considered for inclusion in the review are presented in Table 1 . To be included, studies had to report data on women receiving perinatal group care, that is, care within 1000 days of care from the start of the pregnancy 11 , 28 ; the intervention was centering-based perinatal care, 1 or synonym model known as G-ANC, 2 , 3 , 4 , 5 or similar models like Group Based Antenatal Care, 9 Expect With Me, 8 Pregnancy Circles 10 or Connecting Pregnancy 7 ; the control group was standard individual care; and, studies reported a measure of overall satisfaction with care. Group care is provided during antenatal and postnatal periods; therefore, it is important to examine satisfaction during all stages of perinatal care.…”
Section: Methodsmentioning
confidence: 99%
“…Given the importance of satisfaction in understanding the impact of group care in efforts to expand and scale up the centering-based group care globally, 11 , 28 we examined the quantitative relationship between group care and overall maternal satisfaction compared with standard individual care.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…The innovative implementation research project 'GC during the rst 1000 days (GC_1000)' aims to identify and disseminate contextually appropriate, sustainable mechanisms for implementing GC 24 . For this purpose, GC is implemented in seven countries with preceding contextual analyses.…”
Section: Introductionmentioning
confidence: 99%